Tinjauan Yuridis terhadap Selebgram yang Melakukan Endorse/Promosi Barang Ilegal pada Produk Obat Kosmetik - Kadek Agus Adi Mego; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2021)
Selebgrams are celebrities who exist on lnstagram social media accounts and become public figures on lnstagram social media. The viral figure of celebrities on Instagram is used as an opportunity for business people to endorse/promote cosmetic products through Celegram's Instagram account. However, these activities have a negative impact, namely, the products being promoted are illegal goods that do not have permission from the relevant institutions and this can cause harm to consumers. In terms of writing this research the writer discusses two legal issues, namely the legal arrangement for celebrities who endorse/promote cosmetic medicinal products and legal sanctions against celebrities who endorse/promote illegal goods in cosmetic medicinal products. This research aims to determine the regulations and legal sanctions against celebrities who promote illegal cosmetic medicinal products. This research uses the type of normative legal research, Law No. 8 of 1999, Law No. 19 of 2016, and the Civil Code as a legal basis to determine legal arrangements and legal sanctions against celebrities who endorse/promote illegal goods. The problem approach used is the approach by analyzing legislation related to the problem. The results of this study indicate that the imposition of legal sanctions on celebrities is different from business actors who are producers of these products.